2013
DOI: 10.1155/2013/590456
|View full text |Cite
|
Sign up to set email alerts
|

The Role of DPP4 Activity in Cardiovascular Districts: In Vivo and In Vitro Evidence

Abstract: The introduction of incretin hormone-based therapies represents a novel therapeutic strategy, since these drugs not only improve glycemia with minimal risk of hypoglycemia, but also have other extraglycemic beneficial effects. These agents, which are effective in improving glucose control, could also have positive effects on the incidence of cardiovascular events. The aim of this review is to summarize the present literature about the role of dipeptidyl peptidase 4 (DPP4) in cardiovascular districts, not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…DPP4 is expressed on endothelial cells and seems to play a physiological role in the regulation of vascular tone and angiogenesis. 54 Studies have suggested that DPP4/incretin axis has substantial implication in cardiovascular system ( Figure 3).…”
Section: Effects Of Dpp4i On Endothelial Cells No and Blood Pressurementioning
confidence: 99%
“…DPP4 is expressed on endothelial cells and seems to play a physiological role in the regulation of vascular tone and angiogenesis. 54 Studies have suggested that DPP4/incretin axis has substantial implication in cardiovascular system ( Figure 3).…”
Section: Effects Of Dpp4i On Endothelial Cells No and Blood Pressurementioning
confidence: 99%
“…Thus, increased DPP4 activities in the individuals with high subclinical atherosclerosis risk may not be merely a consequence of enhanced inflammation and oxidative stress. Considering the multiple pleiotropic effects of DPP4 activity and its high expression in circulation and endothelial cells [3,46], the mutual effects between DPP4 activities and other unknown factors might also exert some influence on the development of subclinical atherosclerosis in type 2 diabetes.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The GLP‐1R‐dependent hypothesis is based on the finding that DPP‐4 inhibition, by inducing an increase in GLP‐1, promotes its interaction with GLP‐1R expressed in the endothelium . This event activates a downstream signal transduction that includes cAMP production and K ATP channel activation . The receptor‐independent hypothesis postulates a direct involvement of DPP‐4 in vascular reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 This event activates a downstream signal transduction that includes cAMP production and K ATP channel activation. 24,25 The receptor-independent hypothesis postulates a direct involvement of DPP-4 in vascular reactivity. In line with this latter hypothesis, it has been shown that DPP-4 is expressed in the vascular endothelium 25 and its inhibition induces a direct vasorelaxant effect on isolated vessels in vitro in the presence of GLP-1R antagonist.…”
mentioning
confidence: 99%